DISTRIBUTED DATABASE SYSTEMS: ISSUES IN CONCURRENCY CONTROL, REPLICATION AND FAULT TOLERANCE - Khandal, Rasika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper delves with the great problems in distributed database systems particularly those issues about concurrency control, data replication and fault tolerance. Due to the increase in size of organizations, as well as the need to store, access and retrieve information that is fast, reliable and secure in various locations, distributed databases have been necessitated. Nonetheless, data consistency is very hard to deal with and the challenge of failure and maintain synchronization in multiple sites is very challenging. To get an idea of what is now happening with distributed databases, this paper pinpoints the fundamental issues, reviews the current techniques available and performs a simple statistical analysis.